Competitiveness implications for Ireland of EU enlargement - Barry, Frank; Hannon, Aoife; Hudson, Elaine; KEARNEY, COLM (Statistical and Social Inquiry Society of Ireland, 2003)
Subject to ratification, a further ten states, primarily from Central and Eastern Europe will accede to the EU in May 2004. Another two, and possibly three, CEE states are likely to join in 2007. The present paper assesses the competitiveness implications of this phase of EU expansion for Ireland. Four specific topics are considered: the opportunities for trade and investment expansion, the implications for Ireland?s ability to attract FDI, the likely levels and consequences of immigration from Central and Eastern Europe, and the budgetary implications for the Irish Exchequer.
Read before the Society, 6 February 2003
Keywords: Enlargement; Migration; Trade; Investment; 314.15